On Death and Dying – Forty years later, how well are we dying? - David A. Cameron (South African Family Practice)
In the mid-1960s two doctors, one in London and the other in Chicago, set about changing the accepted medical care of dying patients. In London, Dr Cicely Saunders established St Christopher's Hospice specifically to provide compassionate care for dying patients linked to a rigorous scientific approach to relieving their unpleasant symptoms. Across the Atlantic, in a Chicago Hospital, Dr Elizabeth Kübler-Ross, a psychiatrist who became interested in the emotional issues of dying patients, arranged seminars where dying patients could talk about their feelings. The efforts of these two women led to a totally different way in which modern doctors deal with dying patients. Every medical student is now taught how to break bad news. The knowledge of how to control pain, nausea and other distressing symptoms is available to all doctors. By means of four simple stories, some of the dilemmas of dealing with dying patients in South Africa today will be explored. Forty years after Cicely Saunders and Elizabeth Kübler-Ross introduced their new approaches, how well are we dying?